Characterization of the flip capacitor filter for the XFEL-DSSC project - Facchinetti, Stefano; Bombelli, Luca; Fiorini, Carlo; Porro, Matteo; De Vita, Giulio; Erdinger, Florian (IEEE transactions on nuclear science, 2011)
The European X-ray Free Electron Laser (XFEL) under construction in Hamburg (Germany) will be able to deliver high intensity X-ray pulses of few tens of femto seconds of duration, at 5 MHz pulse repetition rate. Thanks to its characteristics, this instrument will open up new research opportunities for experiments in femto chemistry, structural biology and material research. A high speed focal plane detector system has been presented, based on a novel non-linear DEPFET as a detector. DEPFETs have been chosen since they can provide excellent energy resolution and high speed readout, a fundamental property to cope with the very demanding pulse time structure of XFEL. Full parallel readout is required, with every channel comprising analog filtering, data conversion and memory storage. In this paper we show results for the first prototype of the analog front end that implements the current readout of the DEPFET pixel. The circuit is based on the Flip Capacitor Filter technique, here briefly presented, and has been designed in 130 nm 1.2 V CMOS technology from IBM. Careful characterization of the individual circuit alone and also connected to a single pixel linear detector has been carried out and the measured performance is summarized.
Gesehen am 02.05.2022